HUBUNGAN PELAKSANAAN CLINICAL PATHWAY TERHADAP LAMA RAWAT INAP DAN KEJADIAN FATAL PASIEN SINDROMA KORONER AKUT - NOVI AYUWARDANI (Jurnal Farmasi Indonesia, 2016)
Acute Coronary Syndrome (ACS) is a cardiovascular disease that become a major cause of death until 2020. Standard strategy which summarize the treatment of therapy known as clinical pathways is required caused by the high rate of morbidity and mortality of patients with ACS. This study aimed to determine the relationship of the clinical pathways implementation based on the clinical pathway assessment sheet to the length of stay and number of fatal events in patients with acute coronary syndrome (ACS). This study was a cross sectional study in patients with ACS (NSTEMI/STEMI) treated in ICCU Hospital Dr. Sardjito. The materials used were ACS patient medical records. The tool used is a data collection sheet and clinical pathways assessment sheet. Making retrospective (February - July 2014) and prospective (August - September 2014). The research subjects are 102 patients were divided into 2 groups (49 patients without variation and 53 patients with variations) based on clinical pathways assessment sheet. Variations obtained from the discrepancy amounted to one/more of the therapeutic management of clinical pathways assessment sheet in the first 24 hours of treatment in ICCU. Data analysis includes analysis of long hospitalization relationship to the implementation of clinical pathways in the two groups using the chi-square test and analysis of the relationship number of fatal events (death, heart failure, stroke, and reinfarction) on the implementation of clinical pathways in the two groups using Fisher's exact test. The results of this study indicate that the implementation of clinical pathways based on clinical pathways assessment sheet there is no relationship to the length of stay and the number of fatal events in patients with ACS (p>0,05) in ICCU Dr. Sardjito due ACS assessment sheet clinical pathways are less informative and general management of therapy within the first 24 hours in accordance with the patient's clinical pathways for ACS.